The effect of moderate weight loss on overnight growth hormone and cortisol secretion in healthy female volunteers. - Anderson, I; Crook, W; Gartside, SE; Fairburn, C; Cowen, P (1989)
The effects of moderate weight loss on overnight growth hormone and cortisol secretion were determined in 11 healthy women volunteers who lost an average of 3.1 kg in weight after undertaking a 1000-kcal diet for 3 weeks. There was a reduction in sleep-related growth hormone secretion and an increase in the value of the nocturnal cortisol nadir although mean overnight cortisol secretion was not significantly altered. Moderate weight loss may contribute towards some of the endocrine abnormalities seen in depressed patients.